Development of Loop‐mediated Isothermal Amplification (LAMP) for the Rapid Detection of Streptococcus agalactiae in Tilapia, Oreochromis niloticus. Issue 5 (October 2014) - Ke, Xiaoli; Huo, Huanhuan; Lu, Maixin; Liu, Zhigang; Zhu, Huaping; Gao, Fengying
Abstract Streptococcus agalactiae is one of the major causative agents of tilapia streptococcosis, which has caused severe economic losses in aquaculture. Rapid and accurate detection of the pathogen is necessary to limit losses because of this disease. In this study, a loop‐mediated isothermal amplification (LAMP) assay was developed for the detection of S. agalactiae. Firstly, a set of four primers was designed to target the cfb gene of S. agalactiae. Then, using Bst DNA polymerase, the LAMP assay was performed at 65 C for 60 min and terminated at 80 C for 10 min in a simple water bath. Positive or negative results could be observed by direct visual inspection. There were no cross reactions with other bacterial species, indicating high specificity of the LAMP assay. The sensitivity of the LAMP assay for detecting S. agalactiae was about 20 cells per reaction. Moreover, the developed closed‐tube step has greatly improved the LAMP system. The LAMP method was also applied to detect S. agalactiae in infected tilapia tissue, demonstrating usefulness in diagnostics. Overall, this study showed that the cfb‐based LAMP assay was an effective method to detect S. agalactiae rapidly.